34. Våtvoll: Nyere tids bålplass under heller - Oppvang, Janne (Tromura, 2025)
The stone block at Våtvoll is interpreted as a Sámi cultural heritage site, associated with travel and tradition, with evidence of short-term stays. The site is located in an area with known Sámi clearings from the 17th century onwards and can be linked to travel and outfield use connected to the nearby farms. Charcoal dating indicates at least one stay under the dripline during the period AD 1665–1800. The charcoal shows that there was a hearth under the overhang and that it may have been used multiple times, though it does not indicate how many times or the duration of the stays. However, the overhang appears too small to accommodate longer stays.